2013
DOI: 10.1093/cvr/cvt044
|View full text |Cite
|
Sign up to set email alerts
|

Does low and oscillatory wall shear stress correlate spatially with early atherosclerosis? A systematic review

Abstract: Low and oscillatory wall shear stress is widely assumed to play a key role in the initiation and development of atherosclerosis. Indeed, some studies have relied on the low shear theory when developing diagnostic and treatment strategies for cardiovascular disease. We wished to ascertain if this consensus is justified by published data. We performed a systematic review of papers that compare the localization of atherosclerotic lesions with the distribution of haemodynamic indicators calculated using computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
225
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(236 citation statements)
references
References 65 publications
4
225
1
6
Order By: Relevance
“…[54]). Despite the clear role played by WSS in atherosclerosis, no conclusive evidence of a direct link between low and oscillatory WSS and this pathology [55] has surfaced. WSS, on the other hand, is a manifestation of a more global phenomenon, the flow field as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…[54]). Despite the clear role played by WSS in atherosclerosis, no conclusive evidence of a direct link between low and oscillatory WSS and this pathology [55] has surfaced. WSS, on the other hand, is a manifestation of a more global phenomenon, the flow field as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized though that the WSS vector magnitude needs to be considered to quantify near-wall transport. Recently, the prevailing theory that atherosclerosis is positively correlated with OSI has been challenged [44]. A possible explanation for these inconsistencies may be that many experimental studies impose uniform oscillatory flow in simple settings.…”
Section: P 10mentioning
confidence: 99%
“…The hypothesis that low and oscillatory wall shear stress (WSS) has an atheroprone effect on the endothelial cells lining the inner arterial wall is generally accepted (Asakura and Karino, 1990;Chatzizisis et al, 2007;Ku et al, 1985;Peiffer et al, 2013b). In mouse models of atherosclerosis, it has been shown that atherosclerotic lesions preferentially develop at branching points, bifurcations and at the bends of arteries (Nakashima et al, 1994).…”
Section: Introductionmentioning
confidence: 99%